Comparison between virtual museums - Simona Caraceni (SCIRES-IT, 2014)
Drawing a taxonomy of virtual museum, that can fit to represent all the known cases of virtual museum in the last years, I tried to try my meta-model of classification in two very different examples of virtual museums, to prove the validity of my taxonomical meta-model.